College girls : a century in fiction - Marchalonis, Shirley (Rutgers University Press, 1995)
Since the opening of Vassar College in 1865, objections to higher education for women have ranged from charges that females were mentally and physically incapable of learning to the belief that educating women would destroy society. Underlying all arguments was the folk wisdom which declared that women could not live and work together. To counteract such beliefs, women's colleges tried to create a special kind of space and new role models that would allow women to exist for a short time in idyllic (or, at least, idealized) conditions. The debate over women's education, for the good or ill of society, generated a great deal of "print," including short stories and novels. Shirley Marchalonis guides us through the history of this fiction, its depiction of the complexities of the college experience, and the conflicting attitudes that teetered between fascination and fear, celebration and regret. Using novels, short stories, and some juvenile fiction from 1865 to 1940 - all of it specifically about college "girls"--She examines these ideas, the way they developed over time, and their significance in understanding women's education and women's history. The debate over separate colleges for women continues to this day and can be better understood in the context of this informative and entertaining look at the past